A two-element horn-reflector antenna for cosmic microwave background astronomy. - Dicker, S.R.
We present the design of a novel two-element horn-reflector antenna, which has been used on an interferometer built for studying the anisotropy in the cosmic microwave background at an angular scale of ≈2° and a frequency of 33 GHz. The design consists of a pair of closely packed parabolic mirrors fed by two rectangular corrugated horns, each at an offset angle of 75° to the axis of its mirror. The offset angle and the horn-reflector dimensions were chosen so that the antenna has elliptical primary beams producing a synthesized beam with circular lobes. We have designed and tested the radiation pattern of the individual antennas and the performance of the interferometer using bright radio sources. Our measurements revealed that the individual antennas have low sidelobes and that the crosstalk between the two elements of the interferometer is less than -80 dB. We therefore conclude that this design is suitable for the required astronomical application
Keywords: 30 to 35 GHz; Closely packed parabolic mirrors; Cosmic microwave background astronomy; Elliptical primary beams; Radiation pattern; Radiowave interferometer; Rectangular corrugated horns; Two-element horn-reflector antenna